Sex-specific differences in the association between APOE genotype and metabolic syndrome among middle-aged and older rural Indians - Shilna Azhuvalappil; Raghav Prasad; Pravin Sahadevan; Hitesh Pradhan; Pooja Rai; Jonas S. Sundarakumar (Metabolism Open, 2024)
Background: Metabolic syndrome (MetS), characterized by elevated blood pressure, high blood glucose, excess abdominal fat, and abnormal cholesterol or triglyceride levels, significantly increases the risk of various non-communicable diseases. This study focuses on understanding the sex-specific association between Apolipoprotein E (APOE) polymorphism and MetS among middle-aged and older adults in rural southern India. Methods: This cross-sectional study utilized data from the Centre for Brain Research-Srinivaspura Aging, Neuro Senescence, and COGnition (CBR-SANSCOG) study. Participants (n = 3741) underwent comprehensive clinical assessments and blood investigations, including APOE genotyping. MetS was defined using the National Cholesterol Education Program – Adult Treatment Panel III (NCEP ATP III) and the Consensus criteria. Statistical analyses, including chi-square tests, ANCOVA, and logistic regression, were conducted to explore the association of APOE genotype with MetS and its components, stratified by sex. Results: Females carrying the APOE E4 allele had 1.31-fold increased odds of MetS (95 % CI: 1.02,1.69, p = 0.035) according to the NCEP ATP III criteria but not when the Consensus criteria were applied. The study also noted sex-specific differences in the association of APOE with various MetS components, including lipid levels and waist circumference. Discussion: Our findings reveal a sex-specific association between the APOE E4 allele and MetS, with only females having an increased risk. This study contributes to the understanding of the genetic underpinnings of MetS and highlights the importance of considering sex-specific differences in MetS research and its prevention strategies. This study underscores the complexity of MetS etiology and emphasizes the need for further research to elucidate the role of genetic, environmental, and lifestyle factors in its progression, particularly in sex-specific contexts.